Developmental toxicity of Nafion byproduct 2 (NBP2) in the Sprague-Dawley rat with comparisons to hexafluoropropylene oxide-dimer acid (HFPO-DA or GenX) and perfluorooctane sulfonate (PFOS). (February 2022) - Conley, Justin M.; Lambright, Christy S.; Evans, Nicola; Medlock-Kakaley, Elizabeth; Hill, Donna; McCord, James; Strynar, Mark J.; Wehmas, Leah C.; Hester, Susan; MacMillan, Denise K.; Gray, L. Earl
Graphical abstract: Abstract: Nafion byproduct 2 (NBP2) is a polyfluoroalkyl ether sulfonic acid that was recently detected in surface water, drinking water, and human serum samples from monitoring studies in North Carolina, USA. We orally exposed pregnant Sprague-Dawley rats to NBP2 from gestation day (GD) 14–18 (0.1–30 mg/kg/d), GD17-21, and GD8 to postnatal day (PND) 2 (0.3–30 mg/kg/d) to characterize maternal, fetal, and postnatal effects. GD14-18 exposures were also conducted with perfluorooctane sulfonate (PFOS) for comparison to NBP2, as well as data previously published for hexafluoropropylene oxide-dimer acid (HFPO-DA or GenX). NBP2 produced stillbirth (30 mg/kg), reduced pup survival shortly after birth (10 mg/kg), and reduced pup body weight (10 mg/kg). Histopathological evaluation identified reduced glycogen stores in newborn pup livers and hepatocyte hypertrophy in maternal livers at ≥ 10 mg/kg. Exposure to NBP2 from GD14-18 reduced maternal serum total T3 and cholesterol concentrations (30 mg/kg). Maternal, fetal, and neonatal liver gene expression was investigated using RT-qPCR pathway arrays, while maternal and fetal livers were also analyzed using TempO-Seq transcriptomic profiling. Overall, there was limited alteration of genes in maternal or F1 livers from NBP2 exposure with significant changes mostly occurring in the top dose group (30 mg/kg) associated with lipid and carbohydrate metabolism. Metabolomic profiling indicated elevated maternal bile acids for NBP2, but not HFPO-DA or PFOS, while all three reduced 3-indolepropionic acid. Maternal and fetal serum and liver NBP2 concentrations were similar to PFOS, but ∼10–30-fold greater than HFPO-DA concentrations at a given maternal oral dose. NBP2 is a developmental toxicant in the rat, producing neonatal mortality, reduced pup body weight, reduced pup liver glycogen, reduced maternal thyroid hormones, and altered maternal and offspring lipid and carbohydrate metabolism similar to other studied PFAS, with oral toxicity for pup loss that is slightly less potent than PFOS but more potent than HFPO-DA.